Fungsi Gudang Transit dan Pendistribusian Barang Kebutuhan Kapal Charter - Idelco Febro Rezzikal; DA. Lasse; Marina Iryatie (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
The purpose of this study is to determine and analyze the effect of Freight Forwarding and warehouse services on the distribution of goods needed for vessels to chartered vessels. The method used a quantitative method with the data analysis of multiple linear regression, coefficient analysis, coefficient of determination and hypothesis testing (t-test and f-test). From the analysis and discussion results, there is a proportional relationship between Freight Forwarding services and Transit Warehouse to the distribution of goods which is indicated by the multiple linear regression equation of Y = 6.972 + 0.917 X1 + 0.083 X2. The coefficient determination is 67.9%. The result of the hypothesis test simultaneously shows that the value of F_count = 28.546 is more than F_table = 3.35 because F_count is greater than F_table. It means, Ho is rejected and Ha is accepted. In conclusion, there is a positive influence between Freight Forwarding services and Transit Warehouse on the distribution of goods.